The Zone of Ethnolinguistic Social Networking (ZonES) in Khalaj Turkic: A Model for Language Endangerment - Mehmet AKKUŞ; Çiğdem SAĞIN ŞİMŞEK (Dilbilim Araştırmaları Dergisi)
Social network and ethnolinguistic vitality have been separately studied in various language constellations with different speech communities and participant profiles so far. However, studies focusing on the interplay between social networks and ethnolinguistic vitality are quite scarce, even though the number of endangered languages is increasing in number. Adopting a mixed-hybrid model involving social network theory and ethnolinguistic vitality, this study aims to investigate whether the interplay between language vitality and language use in constructing or maintaining social networks could be observed in Khalaj-Persian by observing 26 multilingual Khalaj-Persian individuals. The data was collected through semi-structured interviews, field work notes, and a language use questionnaire. The effect of generational difference was also manipulated by dividing the participants into three generation groups (older, middle-aged, and younger) based on their ages. The findings revealed that there was an intimate relation between language use in networking and ethnolinguistic vitality for predicting language endangerment with its limitations. The intergenerational analysis showed that the older participants were more inclined to use their heritage language, i.e., Khalaj, with Khalaj-speaking individuals whenever possible, while the younger participants tended to use Persian predominantly in their social networks.